(untitled) (Journal of the College of Basic Education, 2026)
The current research aimed to identify: Preferred supervision styles for the supervising professor, and for graduate students (Master’s, Doctorate). It means the significance of the differences between the preferred supervision styles of the supervising professor and the preferred supervision styles of the graduate student (Master’s, Doctorate). The relationship between the suitability (congruence) between the preferred styles of both the supervising professor and graduate student with the duration of completion of the study in Master’s and Doctoral programs. To achieve the objectives of the current research, the researchers have prepared a tool to measure (styles of supervision favorable to the professor and the student) based on the theory of Gatfield (Gatfield, 2005), the tool consists of (48) style and in front of each style five alternatives are (strongly agree, agree, neutral, disagree, strongly disagree) The scale consists of two sections, one for the supervisor and the other for the student, and the size of the research sample (159) university professors, and (135) graduate students. The psychometric properties of the tool were extracted, and after processing the data obtained from the sample statistically, the following results were reached: Preference for supervision styles for the supervising professor, except for four methods, the preference rate was medium, as well as the case for the graduate student. There is no difference in the preference for the supervision method between the supervising professor and the student. A strong correlation was found in the completion of the student’s study when the supervision style of the supervisor matched that of the graduate student.